Mitotic regulator Nlp interacts with XPA/ERCC1 complexes and regulates nucleotide excision repair (NER) in response to UV radiation. Issue 2 (10th April 2016) - Ma, Xiao-Juan; Shang, Li; Zhang, Wei-Min; Wang, Ming-Rong; Zhan, Qi-Min
Highlights: Mitotic regulator Nlp enhances UV-induced DNA damage repair. Nlp is translocated to nucleus in response to UV-irradiation. Nlp interacts with XPA and ERCC1, and enhances their interaction. Low expression of Nlp is associated with human skin cancers. Abstract: Cellular response to DNA damage, including ionizing radiation (IR) and UV radiation, is critical for the maintenance of genomic fidelity. Defects of DNA repair often result in genomic instability and malignant cell transformation. Centrosomal protein Nlp (ninein-like protein) has been characterized as an important cell cycle regulator that is required for proper mitotic progression. In this study, we demonstrate that Nlp is able to improve nucleotide excision repair (NER) activity and protects cells against UV radiation. Upon exposure of cells to UVC, Nlp is translocated into the nucleus. The C-terminus (1030–1382) of Nlp is necessary and sufficient for its nuclear import. Upon UVC radiation, Nlp interacts with XPA and ERCC1, and enhances their association. Interestingly, down-regulated expression of Nlp is found to be associated with human skin cancers, indicating that dysregulated Nlp might be related to the development of human skin cancers. Taken together, this study identifies mitotic protein Nlp as a new and important member of NER pathway and thus provides novel insights into understanding of regulatory machinery involved in NER.